“THE OATHS” REFLECT SOCIAL RELATIONS - Saminjonov Mukhammadali (Journals Park Publishing, 2023)
In the article, the use of field oaths in social fields, its essence, the role of scientists in studying this field in linguistics, the differences of oaths from each other in terms of fields are presented.
Keywords: In the article, the use of field oaths in social fields, its essence, the role of scientists in studying this field in linguistics, the differences of oaths from each other in terms of fields are presented.